The Use of Contrast Agents in Interventional Pain Procedures: A Multispecialty and Multisociety Practice Advisory on Nephrogenic Systemic Fibrosis, Gadolinium Deposition in the Brain, Encephalopathy After Unintentional Intrathecal Gadolinium Injection, and Hypersensitivity Reactions. (August 2021) - Benzon, Honorio T.; Maus, Timothy P.; Kang, Hye-Ryun; Provenzano, David A.; Bhatia, Anuj; Diehn, Felix; Nelson, Ariana; McCormick, Zachary L.; Liu, Benjamin P.; de Andres Ares, Javier; Anitescu, Magdalena; Blackham, Kristine; et al.
Abstract : This Practice Advisory presents a comprehensive and evidence-based set of position statements and recommendations for the use of contrast media in interventional pain procedures. The advisory was established by an international panel of experts under the auspices of 11 multinational and multispecialty organizations based on a comprehensive review of the literature up to December 31, 2019. The advisory discusses the risks of using gadolinium-based contrast agents. These include nephrogenic systemic fibrosis, gadolinium brain deposition/retention, and encephalopathy and death after an unintentional intrathecal gadolinium injection. The advisory provides recommendations on the selection of a specific gadolinium-based contrast agent in patients with renal insufficiency, those who had multiple gadolinium-enhanced magnetic resonance imaging examinations, and in cases of paraspinal injections. Additionally, recommendations are made for patients who have a history of mild, moderate, or severe hypersensitivity reactions to contrast medium.